PENGARUH KOMITMEN KEPALA DAERAH DAN PENGETAHUAN AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI PROVINSI ACEH - Mahlil Mahlil; M. Rizal Yahya (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The study is aimed to explain the influence of head of local authority and accountancy knowledge regarding to the quality of financial report, in which, measurement in financial report includes reliability, relevancy, understandability and comparability. This study was conducted for Aceh’s representations of BPK-RI auditors who have audited financial reports of Aceh Government. The targeted population in the study was Aceh’s representations of BPK-RI auditors as many as 60 subjects. The type of data that used in the study was primary data taken through questionnaires that directly distributed to the subjects. Meanwhile, the hypothesis that used is tested by doubled linear regression analysis.As a result, through statistical testing and data tabulation via SPSS, it shows that the commitment of head of local authority and accountancy knowledge influenced to the quality of local government reports on finance in Aceh Province.. Keywords: Head of local authority, accountancy knowlegde and quality of financial reports.